NEW TAXA AND LECTOTYPIFICATIONS OF PEDICULARIS (OROBANCHACEAE) REQUIRED FOR THE FLORA OF PAKISTAN - Mill, R. R. (Edinburgh Journal of Botany, 2010)
The new taxa Pedicularis L. series Bicornutae R.R.Mill, Pedicularis series Rhynchotrichae R.R.Mill, Pedicularis bicornuta Klotzsch var. adenocalyx R.R.Mill, Pedicularis murreeana R.R.Mill & R.Bone and Pedicularis staintonii R.R.Mill (Orobanchaceae) are described. Pedicularis series Klotzschianae R.R.Mill is proposed as a replacement name for the illegitimate Pedicularis [unranked] Macranthae that has often been treated as ‘series Macranthae Prain’. The new combination Pedicularis bipinnatifida (Pennell) R.R.Mill is made and four names are lectotypified. An epitype is designated for Pedicularis bicornuta.
Keywords: Epitype; lectotypes; new combination; new series; new species; new variety; Pakistan; Pedicularis